The Role of AI and Machine Translation in Students’ Translation Training - Kałużna, Agnieszka (Research in Language, 2025)
The purpose of this study is to examine what influence the machine translation tools using the elements of Artificial Intelligence (AI) have on students’ translation training. In the theoretical part such notions as machine translation, AI and machine translation education are presented according to Fengqi, Yuxuan (2025), Kruk, Kałużna (2024), Chiu et al. (2023), Bahdanau et al. (2016). The analysis is based on the translation project in which students are asked to compare the applicability of the selected machine translation tools using AI with those machine translation tools that are not equipped with AI. Additionally, students’ interviews are examined as to their opinions about AI machine translation tools in students’ translation training. The findings are scrutinized quantitatively and qualitatively. Finally, conclusions are drawn.